Quality of life and its determinants in women with delayed conception in low-mid socioeconomic neighbourhoods of Northern India: a cross-sectional study - James Kiarie; Sarmila Mazumder; Rita Kabra; Gitau Mburu; Ndema Habib; Ranadip Chowdhury; Neeta Dhabhai; Barsha Gadapani Pathak (BMJ Public Health)
Background The inability to conceive or delay in conception has negative and multidimensional effects on health and well-being, daily functioning and societal interactions. This study assesses the impact of delayed conception on quality of life (QoL) among Indian women with delayed conception and evaluates the Fertility Quality of Life (FertiQoL) questionnaire’s reliability and construct validity in this population.Methodology A cross-sectional study of 1530 women aged 18–30, who had not conceived over a period of 18 months, was conducted in low-to-mid-socioeconomic neighbourhoods in Delhi, India. The 24-item core module of the FertiQoL questionnaire was used to assess participants’ QoL. Researchers analysed data to identify factors associated with QoL scores and evaluated FertiQoL’s internal consistency and validity. Data were collected between July 2020 and August 2021.Result The average FertiQoL score was 31.71 out of 100, indicating a moderately low QoL. Among the subscales, emotional (mean: 29.0) and mind-body domains (mean: 25.4) scored the lowest, while the relational domain scored the highest (mean: 50.7). Factors negatively associated with QoL included a longer duration of delayed conception (β=−0.3, 95% CI: −0.5 to −0.1), husbands fathering children with other partners (β=−1.1, 95% CI: −1.7 to −0.38), domestic violence—emotional (β=−3.5, 95% CI: −4.5 to −2.4), verbal (β=−3.2, 95% CI: −4.7 to −1.7), physical abuse by family (β=−3.6, 95% CI: −5.5 to −1.6), lack of financial support (β=−3.2, 95% CI: −5.2 to −1.2), social pressures (β=−1.6, 95% CI: −2.3 to −0.9) and physical health issues (β=−0.9, 95% CI: −1.7 to −0.2). The FertiQoL tool demonstrated acceptable reliability (Cronbach’s alpha=0.64) and good construct validity (confirmatory factor analysis), confirming its utility in this population.Conclusion Indian women experiencing delayed conception have reduced QoL, particularly in emotional and mind-body domains, due to various psychosocial and socioeconomic challenges. The FertiQoL questionnaire proved to be a reliable and valid tool for assessing QoL in this context. Psychosocial interventions addressing emotional, social and economic stressors are urgently needed to improve their well-being. Future research should include men to better understand the holistic challenges faced by couples struggling to conceive.